Challenges and Achievements of Promoting Rational Use of Drugs in Iran - F Soleymani; M Valadkhani; R Dinarvand (Tehran University of Medical Sciences, 2009)
"nRational use of drugs is one of the major issues in health systems. Analyzing the prescriptions would be of help in recognition of physicians' behavior and population beliefs. The prescriptions were analyzed with "Noskhe Pardaz" software and the major indications in 10 years period between 1998 and 2007 were extracted. The mean item of drugs per prescription, percent of prescriptions including antimicrobials and injectable drugs decreased during study period. Prescriptions including corticosteroids increased. The National Committee of Rational Use of Drugs (NCRUD) activities to educate physicians, general population and children in rational use of drugs were efficient. The results show reduction of irrational use of drugs.